Gendered Development of Motivational Belief Patterns in Mathematics Across a School Year and Career Plans in Math-Related Fields - Dietrich, Julia; Lazarides, Rebecca (Frontiers in Psychology, 2019)
Rooted in Eccles and colleagues’ expectancy-value theory, this study aimed to examine how expectancies and different facets of task value combine to diverse profiles of motivational beliefs, how such complex profiles develop across a school year, and how they relate to gender and career plans. Despite abundant research on the association between gender and motivational beliefs, there is a paucity of knowledge regarding the gendered development of student motivational belief profiles in specific domains. Using latent-transition analysis in a sample of N = 751 ninth to tenth graders (55.9 % girls), we investigated girls’ and boys’ development of motivational belief profiles (profile paths) in mathematics across a school year. We further analysed the association between these profile paths and math-related career plans. The results revealed four motivational belief profiles: high motivation (intrinsic and attainment oriented), balanced above average motivation, average motivation (attainment and cost oriented), and low motivation (cost oriented). Girls were less likely than expected by chance to remain in the high motivation profile, while the opposite was true for boys. The math-relatedness of students’ career plans was significantly higher in the ‘stable high motivation’ profile path than in all other stable profile paths.